2010
DOI: 10.1098/rstb.2010.0075
|View full text |Cite
|
Sign up to set email alerts
|

Combining mathematics and empirical data to predict emergence of RNA viruses that differ in reservoir use

Abstract: RNA viruses may be particularly capable of contributing to the increasing biomedical problem of infectious disease emergence. Empirical studies and epidemiological models are informative for the understanding of evolutionary processes that promote pathogen emergence, but rarely are these approaches combined in the same study. Here, we used an epidemiology model containing observations of pathogen productivity in reservoirs, as a means to predict which pathogens should be most prone to emerge in a primary host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…If we could better predict which viral genotypes or species will successfully emerge in a host population such as humans, we could proactively prepare for inevitable pandemics similar to the current AIDS crisis caused by HIV emergence. We are a long way from accurately predicting emergence events in viral evolution (57), but recent experiments have made inroads.…”
Section: Can Viruses Adapt To Cope With Environmental Change?mentioning
confidence: 99%
See 1 more Smart Citation
“…If we could better predict which viral genotypes or species will successfully emerge in a host population such as humans, we could proactively prepare for inevitable pandemics similar to the current AIDS crisis caused by HIV emergence. We are a long way from accurately predicting emergence events in viral evolution (57), but recent experiments have made inroads.…”
Section: Can Viruses Adapt To Cope With Environmental Change?mentioning
confidence: 99%
“…The virus is normally cultured at 25 • C, but when exposed to heat shock, such as 45 • C for 5 min, roughly 80% of viral particles lose the capacity to productively infect bacteria (57,58), owing to the poor stability of the phage lytic enzyme at high temperature (26). We allowed lineages founded by robust and brittle viruses to evolve on P. syringae pv.…”
Section: Are Viruses More Evolvable Than Cellular Life?mentioning
confidence: 99%
“…But environmental robustness of viruses such as influenza A virus undoubtedly fosters the ability to reside in various host species that may serve as reservoirs that allow occasional spillover into a species of interest such as humans. 52 Robustness may also be relevant in explaining aspects of the current AIDS pandemic. A global increase in robustness has been invoked to explain an apparent global decline in the virulence of HIV-1 strains.…”
Section: Robustness and Modern Rna Virus Pandemicsmentioning
confidence: 99%
“…The results suggested that determination of current niche breadth should be further investigated as a potentially useful indicator in predicting pathogen emergence. 51,52 Because these many recent empirical breakthroughs in the study of robustness have involved microbes, one might predict that infectious disease is the primary biomedical realm where these robustness results might have an immediate, practical impact. Below we describe three examples of biomedically important human disease systems where robustness theory appears highly relevant.…”
Section: Testing Relationships Between Robustness and Pathogen Ementioning
confidence: 99%
“…Froissart et al (2010) review empirical investigations reporting to what extent within-host viral accumulation determines the transmission rate and the virulence of vector-borne plant viruses. Ogbunugafor et al (2010) used an epidemiological model containing observations of pathogen productivity in reservoirs, as a means to predict which pathogens should be most prone to emerge in a primary host such as humans. Related to these two articles, Steinmeyer et al (2010) describe new nested mathematical models studying the epidemiology of a viral disease with dose-dependent replication and transmission by nesting a differential-equation model of the within-host viral dynamics inside a betweenhost epidemiological model.…”
mentioning
confidence: 99%